Lithuania's experience in reducing caesarean sections among nulliparas: the impact of the quality improvement course - Justina Kacerauskiene; Meile Minkauskiene; Tahir Mahmood; Egle Bartuseviciene; Dalia R. Railaite; Arnoldas Bartusevicius; Mindaugas Kliucinskas; Laima Maleckiene; Jonas Ulevicius; Laura Liubiniene; Kastytis Smigelskas; Kornelija Maciuliene; et al. (BMC, 2020)
Abstract Background To evaluate the role of the quality improvement course (QIC) to reduce the caesarean section (CS) rate among nulliparas (Robson groups 1 and 2) and to find out which group of women have reduced the CS rate following attendance at the course. Methods The QIC was organized in 2015. For the evaluation of the CS rate after the OIC, deliveries from the selected hospitals in 2014 and 2016 were compared using MS EXCEL and SPSS 23.0. Results Nulliparas accounted for 44.6% (3585/8046) and 42.9% (3628/8460) of all the deliveries in 2014 and 2016 years, respectively. The CS rate among nulliparas decreased from 19.0% (665/3502) in 2014 to 16.8% (593/3526) in 2016 (p = 0.018). The greatest decrease in absolute contribution to the overall CS rate was recorded in group 1 (p = 0.08). Perinatal mortality was 3.1 in 2014 and 3.9 in 2016 per 1000 deliveries (p = 0.569). Conclusion The QIC has helped to reduce the CS rate among nulliparas without a negative influence on perinatal mortality. The greatest decrease in the overall CS rate was recorded among nulliparous women who were treated with oxytocin and managed to reach a full cervical dilatation.